2021
DOI: 10.1186/s12864-021-07547-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of the poultry red mite, Dermanyssus gallinae, across all stages of the lifecycle

Abstract: Background The blood feeding poultry red mite (PRM), Dermanyssus gallinae, causes substantial economic damage to the egg laying industry worldwide, and is a serious welfare concern for laying hens and poultry house workers. In this study we have investigated the temporal gene expression across the 6 stages/sexes (egg, larvae, protonymph and deutonymph, adult male and adult female) of this neglected parasite in order to understand the temporal expression associated with development, parasitic li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 95 publications
(144 reference statements)
0
4
0
Order By: Relevance
“…Mites have an exoskeleton that contains chitin, and in adults, this chitin creates a sclerotized cuticle layer that is rigid, outlines their body structure, and helps with muscle connection [ 19 ]. Inside their bodies, PRM have a digestive system containing a peritrophic membrane that also consists of chitin and aids blood digestion [ 19 , 50 ]. The inhibition or binding of chitin in this membrane has been successfully employed to control other mite species [ 19 ], and in PRM, the use of the chitin-inhibitor triflumuron under field conditions caused a mite reduction of more than 70% for five months [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mites have an exoskeleton that contains chitin, and in adults, this chitin creates a sclerotized cuticle layer that is rigid, outlines their body structure, and helps with muscle connection [ 19 ]. Inside their bodies, PRM have a digestive system containing a peritrophic membrane that also consists of chitin and aids blood digestion [ 19 , 50 ]. The inhibition or binding of chitin in this membrane has been successfully employed to control other mite species [ 19 ], and in PRM, the use of the chitin-inhibitor triflumuron under field conditions caused a mite reduction of more than 70% for five months [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite D. gallinae being a global and highly debilitating poultry pest, the availability of high-throughput data and experimental platforms is lacking, with only rare exceptions 24,99,100 . We have previously used Illumina RNA-seq data to describe transcriptomes of several tissues of the tick I. ricinus 101-103 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous genotyping of several successive batches of dozens of mites randomly sampled at different locations and times in farm DIN showed that the poultry red mites that develop in this farm only belong to D. gallinae s.s. (more precisely, 100% of the genotyped individuals carried haplotypes of the haplogroup C, very common in French layer farms). 27 Selection of mites to be inoculated into the mesocosms was performed under a stereomicroscope, retaining the largest mites to form a 100% female inoculum as in Bartley et al 28 Only live and active mites were collected, using a P1000 filter pipette tip connected to a vacuum pump. The tips were then sealed with parafilm.…”
Section: Biological Materialsmentioning
confidence: 99%